1988
DOI: 10.3109/00016348809004251
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Iodine Excretion is Low and Serum Thyroglobulin High in Pregnant Women in Parts of Denmark

Abstract: In the Randers area of Denmark urinary iodine excretion (which reflects iodine intake) was found to be much lower than recommended intake levels, both in women in late pregnancy [52(23-118) micrograms iodine/g creatinine, median, range, n = 20] and in non-pregnant controls [42(23-71), n = 20]. Serum thyroglobulin which is high in iodine deficiency was 32.5 micrograms/l (median) (range 10.5-78.0) in the control women and considerably higher in the pregnant women [67.0 micrograms/l (9.0-385)]. This increase was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
3

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 20 publications
2
38
3
Order By: Relevance
“…Seven studies (21,25,30,38,43,45,46) showed that iodine deficient adults had a median Tg ‡13 lg/L (range 16-69 lg/L), while only one study (45) reported that iodine-sufficient adults had a median Tg ‡ 13 lg/L. However, 8 of 12 studies (21,25,(42)(43)(44)72,90,91) reported that adults who were categorized as iodine deficient had a median Tg <13 lg/L.…”
Section: Adultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Seven studies (21,25,30,38,43,45,46) showed that iodine deficient adults had a median Tg ‡13 lg/L (range 16-69 lg/L), while only one study (45) reported that iodine-sufficient adults had a median Tg ‡ 13 lg/L. However, 8 of 12 studies (21,25,(42)(43)(44)72,90,91) reported that adults who were categorized as iodine deficient had a median Tg <13 lg/L.…”
Section: Adultsmentioning
confidence: 89%
“…Two of the eight studies (78,79) assessed Tg concentration in iodine-deficient women throughout their pregnancy (i.e., in each trimester); in one study (79), a median Tg <13 lg/L was observed in all three trimesters, and in one study (78), a Tg ‡13 lg/L was reported in the first and third trimesters, but it was <13 lg/L in the second trimester. Although six of eight studies (37,38,74,75,77,79) collected information on the use of iodine supplements in pregnancy, of these, only one study (37) reported that the Tg concentration of women taking iodine supplements was significantly lower compared with women who did not take supplements (i.e., difference of *15 lg/L). We are unaware of any published studies of pregnant women with adequate iodine status that include measures of both UIC and Tg.…”
Section: Pregnant Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then RIAs and screening for Tg autoantibodies (Tg-Ab) were improved (12) and several studies found an inverse association between iodine intake and serum Tg (13,14,15,16,17). Therefore, it has been suggested that serum Tg values in a population is a sensitive marker of iodine intake, and that serum Tg can be used to monitor the iodine status of a population.…”
Section: Introductionmentioning
confidence: 99%